2007
DOI: 10.1136/tc.2006.018119
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke levels in Scottish pubs: the effect of smoke-free legislation

Abstract: Objective: To compare levels of particulate matter, as a marker of secondhand smoke (SHS) levels, in pubs before and 2 months after the implementation of Scottish legislation to prohibit smoking in substantially enclosed public places. Design: Comparison of SHS levels before and after the legislation in a random selection of 41 pubs in 2 Scottish cities. Methods: Fine particulate matter ,2.5 mm in diameter (PM 2.5 ) was measured discreetly for 30 min in each bar on 1 or 2 visits in the 8 weeks preceding the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
104
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 15 publications
6
104
2
6
Order By: Relevance
“…The validity of particulate matter with an aerodynamic diameter of up to 2.5 mm (PM 2.5 ) as indicator for exposure to SHS is confirmed by studies showing a high correlation between concentrations of PM 2.5 and SHS-specific compounds (Bolte et al, 2008) or comparing PM 2.5 levels between venues with different degrees of smoking restriction (Brauer & Mannetje, 1998;Connolly et al, 2009;Repace et al, 2006;Semple et al, 2007;Travers, 2004). The mass concentration of suspended particles is measured in micrograms per cubic meter.…”
Section: Brief Reportmentioning
confidence: 73%
See 1 more Smart Citation
“…The validity of particulate matter with an aerodynamic diameter of up to 2.5 mm (PM 2.5 ) as indicator for exposure to SHS is confirmed by studies showing a high correlation between concentrations of PM 2.5 and SHS-specific compounds (Bolte et al, 2008) or comparing PM 2.5 levels between venues with different degrees of smoking restriction (Brauer & Mannetje, 1998;Connolly et al, 2009;Repace et al, 2006;Semple et al, 2007;Travers, 2004). The mass concentration of suspended particles is measured in micrograms per cubic meter.…”
Section: Brief Reportmentioning
confidence: 73%
“…Air Contamination Due to Smoking in German Restaurants, Bars, and Other Venues-Before and After the Implementation of a Partial Smoking Ban of respirable suspended particles (Brauer & Mannetje, 1998;Connolly et al, 2009;Ellingsen et al, 2006;Goodman et al, 2007;Hyland, Travers, Dresler, Higbee, & Cummings, 2008;Johnsson et al, 2006;Repace et al, 2006;Semple et al, 2007;Travers, 2004).…”
Section: Brief Reportmentioning
confidence: 99%
“…Studies conducted in the United States, Scotland and Italy reported reductions in indoor PM 2.5 levels of 95%, 86% and 64%, respectively, after indoor smoking was banned [17][18][19]. These policies have also been found to lead to immediate improved health outcomes among venue employees as well as the general public.…”
Section: Discussionmentioning
confidence: 97%
“…Other contributors, such as cooking, may have influenced PM 2.5 measurement. However, evidence shows that smoking, and not cooking emissions, is the overwhelming source of indoor PM 2.5 [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Airborne markers, such as vapour-phase nicotine or respirable suspended particles indicate the mean exposure level in a specific setting, and are easier to obtain than biological samples [8]. Among respirable suspended particles, those with a 50% cut-off aerodynamic diameter of 2.5 mm (commonly known as fine particles or PM2.5) are widely used for SHS assessment in enclosed settings [9][10][11]. PM2.5 originate from all types of combustion, including motor vehicles, residential wood burning, forest fires, some industrial processes, etc.…”
mentioning
confidence: 99%